THE IMPACT OF MARKETING STRATEGY ON CUSTOMER SATISFACTION: A STUDY OF PARLEVLIET PARABA SEAFOOD (PPS) IN INDONESIA - Sumule, Jusriana Sartika (UKI Toraja Press, 2023)
Parlevliet Paraba Seafood is one of the biggest seafood company from center of Indonesia with more than 15 years experience in seafood business and have been take part in exporting seafood raw material products to all over the world. The purpose of this research is to analyze the marketing strategy of Parlevliet Paraba Seafood towards customer satisfaction by collect the data of product strategy, pricing strategy, distribution strategy, and promotion strategy. This research using a quantitative approach that focuses on testing hypotheses, analyzing measured data and the conclusions generated are generalizations. The data used is primary data, which is data collection carried out using a questionnaire given directly to the respondents. The respondents are the customers of the Parlevliet Paraba Seafood itself. The research sample is the customer who at least purchase the product five times annually in the period of 2016-2018. The data collection technique in this study is to use the survey method by online questionnaires. The e-questionnairs mainly have 2 parts. The first part is to get the information about the respondent’s biography, and the second part concerns about the customer knowledge and experience of marketing strategy offered by the company and its effect to customer satisfaction. Data analysis used multiple linear regression analysis to examine the impact of independent variables on the dependent variable. According to the result of this research, each of the independent variable have positive impact on customer satisfaction